Fluctuations in instantaneous frequency predict alpha amplitude during visual perception - Stephanie Nelli (Nature Portfolio, 2017)
Though the amplitude and frequency of neural oscillations in the alpha band are related to dissociable visual processes, they are not independent mathematically. Here, the authors show that fluctuations in instantaneous frequency predict alpha amplitude during visual discrimination tasks.